Dyspnea caused by a giant retroperitoneal liposarcoma: A case report - Ioannidis, Argyrios (Oncol Lett, 2018)
Liposarcomas are the most common soft tissue tumors with various histological subtypes. They usually appear in the retroperitoneal region of the abdomen, but their symptomatology remains unclear and their diagnosis, as well as treatment challenging. A case of a 55-year-old female patient with dyspnea and light diffuse abdominal pain caused by a giant retroperitoneal liposarcoma is presented. The patient had an unremarkable medical history, while the computed tomography scan revealed a large mass at the right portion of the abdomen, with its upper limits to the lower edge and the gate portion of the liver. The mass was in contact with the right kidney, the inferior vena cava and the right renal vein, causing mild dilation of the right kidney pelvis. Without any evidence of intra-abdominal metastases, the tumor was surgically resected. The histological analysis of the tumor revealed a well-differentiated liposarcoma. The patient had an uneventful recovery and was discharged on the 10th postoperative day. Until today (4 years later) she remains asymptomatic, without any signs of recurrence. The retroperitoneal liposarcoma is a clinical entity with unclear clinical symptoms and the physician should consider including it in the differential diagnosis of a majority of symptoms, such as dyspnea.